CODE MIXING IN HOT 20 COUNTDOWN OF PRAMBORS RADIO PROGRAM - Berlin Sibarani, DwiAstarini and (LINGUISTICA, 2015)
This study deals with code mixing used by broadcasters in Prambors Radio, namely Hot 20 Countdown and SelamatPagi program. The objectives of the study were (1) to find out the types of code mixing in Hot 20 Countdown and SelamatPagi, (2) to find out in what context code mixing used in Hot 20 Countdown and SelamatPagi. The data of this study were the conversation between the broadcasters. This study applied descriptive qualitative method. The findings shows that there were 68 sentences of code mixing which were classified into three types of code mixing, in Hot 20 Countdown there were 46 sentences, it consists of 30 utterances (65,22%) insertion of code mixing, 15 utterances (32,61%) alternation of code mixing and 1 utterance (2,17) lexicalization of code mixing, while in SelamatPagi program there were 26 utterances, it consist 17 utterances (77,27) of insertion code mixing, 4 utterances (4,55%) of alternation code mixing, and 1 utterance (4,55%) of lexicalization code mixing.